Developing Managerial Skill for Profitable Farming Business - Mehta, Sumit (Indian Journal of Marketing, 2004)
Traditionally, Indian farmers relied upon human and animal operated equipment for agricultural production and for processing activities. But with the introduction of tractors and agricultural equipment, there has been a spectacular rise in agriculture production. Therefore, agricultural implements and machines have been considered the most important input for increasing the productivity and production. Under the present scenario of globalization and competitiveness, we have to reduce the cost of cultivation and increase the profitability. This can be possible if we consider Management as a tool for optimal use of Mechanization Technology for enhancing profitability of farmers.